4(x+2)=2(2x+1)+6

Simple and best practice solution for 4(x+2)=2(2x+1)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)=2(2x+1)+6 equation:


Simplifying
4(x + 2) = 2(2x + 1) + 6

Reorder the terms:
4(2 + x) = 2(2x + 1) + 6
(2 * 4 + x * 4) = 2(2x + 1) + 6
(8 + 4x) = 2(2x + 1) + 6

Reorder the terms:
8 + 4x = 2(1 + 2x) + 6
8 + 4x = (1 * 2 + 2x * 2) + 6
8 + 4x = (2 + 4x) + 6

Reorder the terms:
8 + 4x = 2 + 6 + 4x

Combine like terms: 2 + 6 = 8
8 + 4x = 8 + 4x

Add '-8' to each side of the equation.
8 + -8 + 4x = 8 + -8 + 4x

Combine like terms: 8 + -8 = 0
0 + 4x = 8 + -8 + 4x
4x = 8 + -8 + 4x

Combine like terms: 8 + -8 = 0
4x = 0 + 4x
4x = 4x

Add '-4x' to each side of the equation.
4x + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| f(x)=-x^3-2 | | 1.25+6x= | | 6.95-(1.95+0.10x)=0 | | -2(6+9)= | | 5x+11=5x-21 | | 4x^2+(31x)=0 | | 13-(x+8)=6x+2 | | 14.25/5 | | 14.25/4 | | 0.75x+.05(2-x)=10(43) | | -2(x+6)=0,5-14 | | 3x^2=5-2 | | 8399840909205709x=897979070979797009-5 | | 9=-27+4x | | -7-6x+2=-(x-4).+2(x+6) | | 4/3x=-3 | | -3(2t-5)+2t=5t | | 10=-27+4x | | 2x^2+4ax+3x+6a=0 | | 3468666765x-558575858=68687763456789+56789 | | 2x/5=-2 | | (3-x).5+8=18 | | 2x/5 | | -84-10x=56-38x | | 2x+37=4x+1 | | 300-2x=50+5x | | X^3-52-96=0 | | y=-27+4x | | 2(2x-1)-3(x-5)=5x-3(2x-7)+8 | | y+8y=8 | | y+8y=7 | | 5x=-32.15 |

Equations solver categories